Chemical Kindling with Pentylenetetrazole and Effects of Equeous Extract of Humulus Lupulus Flowers on the Kindling Process in the Male Mice - S Namvar Aghdash; S Nasirifard; F Safari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2015)
Introduction: More than 1% of world population suffer from epilepsy, which affects many aspects of individuals’ life. In fact, multiple treatment methods are used for this disorder, among which treatment effects of herbal plants can be introduced. Humulus Lupulus has been utilized in the traditional medicine as an anti-convulsion herb. Therefore, this study aimed to investigate the anti-convulsive effect of Humulus Lupulus extract on the pentylenetetrazole (PTZ) kindling model of epilepsy.